The creating and developing Buddhist happiness indicators according to the Buddha’s principle of teaching. - Oboun, Phramaha Suthit (Journal of International Buddhist Studies, 2015)
The research on “the creating and developing Buddhist happiness indicators according to the Buddha’s principle of teaching” has 3 objectives, which are 1) to analyze the components and the indicators of happiness according to the principle of Buddhism; 2) to create and test the form for the measurement of people’s happiness according to the principle of Buddhism; 3) to present the pattern and the methods to enhance happiness according to Buddhist happiness indicators. This study is a mix research which combines the studies of documents, quality and quantity. The results of the study were as follows : According to the Buddhist point of view, human life would have to experience both happiness and suffering. Buddhism focused on the practice to reduce suffering, to understand the causes of suffering and to search for the real happiness. In Buddhist viewpoint, the happiness which depended on materials or the joy of erotic pleasure was not permanent and easy to change. Happiness was connected to the principle of life development which comprised physical pleasure, moral pleasure, emotional pleasure and intellectual pleasure. Therefore, the components and the indicators of happiness according to the principle of Buddhism were related to the 4 aspects of life development principle as mentioned before. A person must determine his role and duty accurately and righteously, and he must be responsible for his duty and his own action. Also, he must have morality and honesty as the foundation of life. When a person avoids evil things and does good things, he is sure to be blessed with happiness and is able to block the ways that lead to suffering; Therefore, the enhancement of happiness is related to the understanding of the way of emergence and embellishment of natural conditions and 4) Happiness is related to the development of mind and wisdom of individuals and societies which is in accordance with the principle of Buddhism based on the right mental attitude.